Evidence for energetic particle precipitation and quasi-biennial oscillation modulations of the Antarctic NO 2 springtime stratospheric column from OMI observations - E. M. Gordon; A. Seppälä; J. Tamminen (Atmospheric Chemistry and Physics, 2020)
Observations from the Ozone Monitoring Instrument (OMI) on the Aura satellite are used to study the effect of energetic particle precipitation (EPP, as proxied by the geomagnetic activity index, A p ) on the Antarctic stratospheric NO 2 column in late winter–spring (August–December) during the period from 2005 to 2017. We show that the polar (60–90 ∘ S) stratospheric NO 2 column is significantly correlated with EPP throughout the Antarctic spring, until the breakdown of the polar vortex in November. The strongest correlation takes place during years with the easterly phase of the quasi-biennial oscillation (QBO). The QBO modulation may be a combination of different effects: the QBO is known to influence the amount of the primary NO x source ( N 2 O ) via transport from the Equator to the polar region; and the QBO phase also affects polar temperatures, which may provide a link to the amount of denitrification occurring in the polar vortex. We find some support for the latter in an analysis of temperature and HNO 3 observations from the Microwave Limb Sounder (MLS, on Aura). Our results suggest that once the background effect of the QBO is accounted for, the NO x produced by EPP significantly contributes to the stratospheric NO 2 column at the time and altitudes when the ozone hole is present in the Antarctic stratosphere. Based on our findings, and the known role of NO x as a catalyst for ozone loss, we propose that as chlorine activation continues to decrease in the Antarctic stratosphere, the total EPP- NO x needs be accounted for in predictions of Antarctic ozone recovery.